2020
DOI: 10.1177/0961203320947149
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of subclinical synovitis of the hand in patients with systemic lupus erythematosus

Abstract: Objectives To determine the prevalence of subclinical synovitis in Lupus patients without peripheral joint symptoms, in those with arthralgias without arthritis and those with episodic arthritis but without radiological structural damage. Methods We conducted a multicentre cross-sectional study. Patients with lupus from those three categories were recruited to take part in a greyscale ultrasound scan performed by an expert blinded rheumatologist. Data from a historical control group from a previous study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…[6,10] Most studies conducted to date have found a significant subclinical joint involvement of metacarpophalangeal, proximal interphalangeal, and wrist joints in patients with SLE leading to the conclusion that reliance only on physical examination of the joints may underestimate the presence of active joint inflammation. [8,16–19] On the other hand, subclinical synovitis did not show a clear correlation with disease activity parameters. Although earlier studies mainly found mild changes in asymptomatic patients, [17] a recent US study reported subclinical synovitis grade ≥2 in 20.8% of patients.…”
Section: Discussionmentioning
confidence: 88%
“…[6,10] Most studies conducted to date have found a significant subclinical joint involvement of metacarpophalangeal, proximal interphalangeal, and wrist joints in patients with SLE leading to the conclusion that reliance only on physical examination of the joints may underestimate the presence of active joint inflammation. [8,16–19] On the other hand, subclinical synovitis did not show a clear correlation with disease activity parameters. Although earlier studies mainly found mild changes in asymptomatic patients, [17] a recent US study reported subclinical synovitis grade ≥2 in 20.8% of patients.…”
Section: Discussionmentioning
confidence: 88%
“…The prevalence of subclinical synovitis in heterogenous studies, including—in most of them—consecutive, both symptomatic and asymptomatic, patients with lupus, ranges between 10% and 95% [ 8 ]. Honghu et al [ 2 ], in a retrospective study, aimed to compare the role of hand and wrist US in diagnosing subclinical synovitis in SLE patients.…”
Section: Update On Imaging Of Sle On Radiography Ultrasonography and Mrimentioning
confidence: 99%
“…Twelve patients (29.3%) demonstrated knee joint involvement. Guillen et al [ 8 ], in a multicenter cross-sectional study, found US features of arthritis in hands in about one-third of asymptomatic SLE patients with synovial thickening on gray scale images, while synovial hyperemia on power Doppler US was seen in one-fifth of the patients. The global prevalence of subclinical synovitis in the group with arthralgias was 38.2%.…”
Section: Update On Imaging Of Sle On Radiography Ultrasonography and Mrimentioning
confidence: 99%
See 2 more Smart Citations